2
$\begingroup$

While reading through my textbook, I came across this particular equation: $$ x = x\log (y) + \log (y) $$ But they solve it by doing this: $$ x = x\log (y) + \log (y) $$ $$ x = (x + 1)\log(y) $$ $$ \frac {x}{x+1} = \log(y) $$ $$ y = 10^{\frac{x}{x+1}} $$ Which is fine, but I don't understand why they didn't do it like this: $$ x = x\log (y) + \log (y) $$ $$ x=\log(y^x)+\log(y) $$ $$ x=\log(y^{2x}) $$ $$ x=2x\log(y) $$ $$ \frac{x}{2x}=\log(y) $$ $$ y=10^{\frac{x}{2x}} $$ I'm confused over which one is correct.

$\endgroup$
1
  • $\begingroup$ Yep, I feel like an idiot! Thanks, shost71 and MPW! $\endgroup$
    – dr_nefario
    Commented Mar 16, 2015 at 2:34

3 Answers 3

2
$\begingroup$

I think you have got an error: $ x = log(y^x) + log(y) = log(y^x\cdot y) = log(y^{x+1})$

$\endgroup$
1
$\begingroup$

You've made an error.

$\log y^x +\log y$ is $\log y^{x+1}$, not $\log y^{2x}$

$\endgroup$
1
$\begingroup$

When you do $$ log(y^x) + log(y) $$ this equals: $$ log(y^x \cdot y) = log(y^{x+1}) $$

which gives $ y = 10^{\frac{x}{x+1}} $

$\endgroup$

You must log in to answer this question.

Not the answer you're looking for? Browse other questions tagged .